2011
DOI: 10.1016/j.porgcoat.2010.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Paint systems formulated with ion-exchange pigments applied on carbon steel: Effect of surface preparation

Abstract: Ion exchange pigments are a scientifically very interesting alternative to chromates thathave not yet been fully explored. This study considers the following candidate anticorrosive pigments: calcium-exchanged silica (Si/Ca), hydrotalcite/vanadate (HT/V) and calcium bentonite (Bentonite/Ca).Paint systems manufactured with these ion exchange pigments have been subjected to accelerated corrosion laboratory tests: humidity condensation (HC) and salt fog (SF), simulating environments of low and high corrosivity, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This inhibitor is typically prepared by treatment of SiO2 powder with calcium hydroxide (Ca(OH)2) [19]. Several studies showed that the corrosion protection of steel with Ca +2 -SiO pigments could be as good as using conventional chromate species in certain conditions [20,21]. It is known that silicates form complex colloidal structures in an aqueous environment [22].…”
Section: Introductionmentioning
confidence: 99%
“…This inhibitor is typically prepared by treatment of SiO2 powder with calcium hydroxide (Ca(OH)2) [19]. Several studies showed that the corrosion protection of steel with Ca +2 -SiO pigments could be as good as using conventional chromate species in certain conditions [20,21]. It is known that silicates form complex colloidal structures in an aqueous environment [22].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their porous structure and a high specific surface area with OH groups on the surface, silica particles can be modified with inhibitive species, metallic ions, and others by ion-exchange reactions [7, 12−14]. Granizo et al used 10−15% of calcium-exchange silica (Si/Ca) as an inorganic pigment loaded in alkyd coatings to improve adhesion performance and anticorrosion properties for carbon steel substrates [15,16]. Due to cationic-exchange reactions, calcium ions can be released from the corrosive environment and, then, form complex silicate products, such as CaSiO3•FeSiO3, which suppress the corrosion process.…”
Section: Introductionmentioning
confidence: 99%
“…This has become a major challenge since the last decade for all sectors involving metallic protection (Granizo, 2011). Among various alternatives, ferrite pigments have been introduced as possible replacement of chromate coatings (Jaskova, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of anticorrosive primer paints, there is growing interest to find environmentally friendly anticorrosive pigments to replace Cr (VI) pigments which have hazard effect on both the environment and human health. This has become a major challenge since the last decade for all sectors involving metallic protection (Granizo, 2011). Among various alternatives, ferrite pigments have been introduced as possible replacement of chromate coatings (Jaskova, 2012).…”
Section: Introductionmentioning
confidence: 99%